Critical Thinking Skills of Students of SMP 1 Angkinang on the Ecosystem Concept - Siti Noor Ismi Sa’dah; Aminuddin Prahatamaputra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Critical thinking is a skill that is achieved through a process not an inherited trait by parents to their children. An effort to teach how to think critically at school as early as possible is needed. This research aimed to describe the worthiness of biology learning tools to the students' critical thinking and the implementation in learning on the ecosystem concept at SMP 1 Angkinang. This study is a Research &Development (R & D) in which the first phase is the development of tools using 4-D models. In the second phase,the worthiness assessment is done by the validator, small group testing, and field testing. Learning toolsaredeveloped using the environmental approach onecosystem concept to critical thinking skill. Worthiness test results obtained by the average value of 2.61 (fair valid). In the small group of test data obtained to formulate the problem 72.50 (medium), formulating hypotheses 76.25 (good), collect data 66.85 (medium), analyzed data 88.15 (good) and concludes 68.15 (medium) , In the field test data obtained to formulate the problem 71.35 (medium), formulating hypotheses 82.50 (good), collect data 83.15 (good), analyzed data 84.85 (good) and concludes 87.35 (good).Keywords:  Critical Thinking Skills, Ecosystem, SMP 1 Angkinang